Study on Phase Transformation Dynamics, Microstructure, and Properties of the Cu-2.7Ti-2.5Ni-0.8V Alloy - Jia Liu; Jituo Liu; Xianhui Wang (Archives of Metallurgy and Materials, 2023)
The phase transformation dynamic and electrical conductivity equations of the aged Cu-2.7Ti-2.5Ni-0.8V alloy were established in this work. The microstructure evolution and precipitated phases were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The mechanical properties were tested using a hardness testing machine and universal test machine, and the electrical conductivity was measured by the eddy conductivity gauge. The results show that NiTi intermetallic compounds are formed during the solidification, and these phases such as Ni3Ti and NiV3 are precipitated after aging treatment. The fracture morphology displays that a large number of shallow and equiaxed dimples occur on the tensile fracture, indicating a typical ductile fracture. After aging treatment at 450°C for 240 min, the hardness, tensile strength, elongation and electrical conductivity of the Cu-2.7Ti-2.5Ni-0.8V alloy are 184 HV, 459 MPa, 6.3% and 28.72% IACS, respectively.